Excel-Parle-Farmers: a case of Partnership - Vikram Singh,; G Bhaskar, (Journal of Agricultural Extension Management, 2025)
Even after 59 years of independence, the quality of life of the Indian farmer has not improved as much as expected. The reasons for such a situation are not too far to seek. The terms of trade have never been favourable to agriculture and hence there has been no capital formation in the sector, which eventually resulted in lack of infrastructure creation leaving agriculture as a non-remunerative enterprise with absolutely stunted growth. Under these circumstances it is only towards the end of 10th plan period, the first time in the history of independent India, that the growth in Agriculture has recorded a rate of 1.8 percent against the projected annual growth rate of 4 percent. Thanks to the green revolution (37 years ago in late sixties) the country is able to reach self-sufficiency in food grains. In the last one decade the number of farmers' suicides have risen, water table has dropped, crop yields are stagnant, cost of farm inputs, implements, diesel have increased, land holdings fragmented and credit flow is scarce clutching the farmer in an all-round trap